‘No King in Israel’: Narrative Criticism and Judges 17-21 - Satterthwaite, Philip E. (Tyndale bulletin, 1993)
Scholars such as Robert Alter and Meir Sternberg have produced suggestive interpretations of sections of Old Testament narrative. This article applies their techniques to the stories in Judges 17-21, and argues that these techniques yield a coherent interpretation of the chapters, paying attention to features such as repetition, narrative analogy, and the use of narration and dialogue. It subsequently deals with some implications of this interpretation, according to which the narrator takes a negative view of pre-monarchic Israel.